2017
DOI: 10.5194/aab-60-205-2017
|View full text |Cite
|
Sign up to set email alerts
|

Milk fatty acid composition as an indicator of energy status in Holstein dairy cows

Abstract: Abstract. Transition dairy cows often enter a stage of negative energy balance during which the utilization of energy reserves is reflected in the milk fatty acid (FA) composition. In this study, metabolic status was evaluated by measuring milk FA, ruminal short-chain FA (RSCFA), and serum biochemical parameters in Holstein cows. Samples (milk, rumen contents, and blood) were collected around days 30 (early) and 150 (middle) of lactation, and rumen contents and blood samples were collected 30 days before calvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
2
18
2
Order By: Relevance
“…Thus, the beginning of lactation is the most demanding period in terms of energy status and also herd health management [ 83 , 86 , 96 , 97 ]. High utilization of energy reserves during this period is reflected in milk fat content [ 98 ], namely in the FA composition and mutual ratios between individual FA groups [ 99 ].…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the beginning of lactation is the most demanding period in terms of energy status and also herd health management [ 83 , 86 , 96 , 97 ]. High utilization of energy reserves during this period is reflected in milk fat content [ 98 ], namely in the FA composition and mutual ratios between individual FA groups [ 99 ].…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
“…With improvements in energy balance through progression of lactation or increased feed intake, the FA profile of milk markedly changed [ 81 ]. A significantly higher proportion of SFAs, described around day 150 pp, was associated with the later stages of lactation [ 97 ], when animals were no longer in NEB. Similarly, the lower proportion of MUFAs around day 150 pp indicates a well-balanced energy intake in cows [ 99 ].…”
Section: Effects Of Nutrition and Metabolic Aspects Of Cattle On Mmentioning
confidence: 99%
“…Several studies have shown that the concentrations of milk LCFA, especially C18:0 and C18:1 cis-9, are effective predictors of cow ES (Stoop et al, 2009;Gross et al, 2011;Jorjong et al, 2014;Vranković et al, 2017). Jorjong et al (2014) suggested that an elevated concentration of C18:1 cis-9 in milk fat in the second lactation week could act as an early warning of a risk of detrimentally high blood NEFA.…”
Section: Milk Fa Composition Traits As Plasma Nefa Predictorsmentioning
confidence: 99%
“…The high uptake of LCFA by the mammary gland inhibits de novo synthesis of short-chain FA and medium-chain FA (MCFA), causing changes in milk FA composition (Palmquist et al, 1993;Stoop et al, 2009;Gross et al, 2011). Thus, several studies have examined milk composition and especially milk FPR, as well as milk FA concentrations or ratios of individual FA, as ES indicators (de Vries and Veerkamp, 2000;Heuer et al, 2000;Reist et al, 2002;Friggens et al, 2007;Gross et al, 2011;Dórea et al, 2017;Vranković et al, 2017). Milk composition and its changes are good candidates for ES predictors because they can be measured from routinely collected test-day milk samples at low cost by mid-infrared spectroscopy (MIR).…”
Section: Introductionmentioning
confidence: 99%
“…Matsumoto et al (2014) found that the SNP (g. −823G > A) in the FADS2 promoter had a significant effect on several beef quality traits, including beef marbling score, whereas Takahashi et al (2016) reported a highly significant association between the rs211580559 SNP in exon 7 of the FADS2 gene and intramuscular C18:2(n-6) composition. In the transcriptomic study, Wang et al (2017) pointed to FADS2 as a strong candidate gene that may be associated with intramuscular fat deposition. Recently, Gol et al (2018) reported that the polymorphism in the porcine FADS2 gene is linked to arachidonic acid metabolism.…”
Section: Introductionmentioning
confidence: 99%